The relationship of syntactic complexity and rhetorical move-steps in research article discussions: A comparative analysis of Chinese and native English writers - Yuan Zhang; Zewen Wang (PLoS ONE, 2025)
This study seeks to identify the differences in syntactic complexity (SC) across rhetorical move-steps in the discussion section of research articles (RAs) written by Chinese and native English writers. The corpus consisted of 200 RA discussion sections from the field of Applied Linguistics. Each sample was manually annotated for rhetorical move-steps using the seven-move framework of RA discussion proposed by Yang and Allison (2003). The results revealed that distinct SC patterns across rhetorical move-steps, with differences most pronounced at the phrasal-level complexity. Chinese writers demonstrated greater SC performance in M2 Reporting results , M4S1 Interpreting results , M4S2 Comparing results with literature , and M4S3 Accounting for results , characterized by compressed noun phrases (NPs) through significantly more frequent use of pre-modifier sequences and multiple-level prepositional phrases. In contrast, native English writers presented greater SC in M3 Summarizing results , M4S4 Evaluating results , M5 Summarizing the study , M6S2 Indicating significance/advantage , M7S1 Making suggestions , and M7S2 Recommending further research , distinguished by more extensive use of complex NPs with both phrasal and clausal modifiers. Implications for L2 academic writing practice and pedagogy are discussed.